Causative Organisms in Neonatal Sepsis and Their Antibiotic Sensitivity and Resistance Pattern - Nadia Mazhar, Ammara Ayub, Sajid Ali Shah, Sehrish Anjum, Saeed Zaman, Lutfullah Goheer (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine different causative organisms confirmed through blood culture in babies presenting with neonatal sepsis and their antibiotic sensitivity and resistance pattern. Methodology: This cross sectional observational study was conducted at The Department of Neonatology, Holy Family Hospital, Rawalpindi from Jan 2020 to Jan 2021. During the study period, a total of 241 neonates with positive blood culture were included. After following aseptic measures blood sample of 2.5ml was taken from neonate with features of sepsis. Samples were sent to microbiology sector while organism grown on culture media was noted and their sensitivity was checked for commonly used antibiotics. Results: There were 110(45.64%) female and 131(54.36%) male. Most common organism was staphylococcus aureus i.e. 29.88% (72/241) followed by klebsiella pneumonia and pseudomonas in 17.43% each, salmonella typhi 14.52% Acinetobacter 8.3%, E.coli 7.475 and enterococcus 4.98%. Drug sensitivity was assessed and found that drug Sulzone was 80% to 100% sensitive for pseudomonas, salmonella typhi and Acinetobacter organisms and 71.4% sensitive for klebsiella pneumonia negative organism while ciprofloxacin and Imipenem was sensitive for E.coli Conclusion: The most common causative organism of neonatal sepsis was staphylococcus aurues followed by klebsiella pneumonia and pseudomonas. Sulzone (cefoperazone/sulbactum) was found to be the most sensitive drug.